In silico and physico-chemical characterization of cluster formation dynamics in peptide solutions - Dimitar Kaynarov; Karina Marinova; Rossitsa Marinova; Peicho Petkov; Lyudmila Velkova; Aleksandar Dolashki; Petar Petrov; Leandar Litov; Elena Lilkova; Pavlina Dolashka; Nevena Ilieva (Biochemistry and Biophysics Reports, 2024)
Although antimicrobial peptides are considered one of the most promising alternatives to conventional antibiotics given the alarming increase in bacterial multidrug resistance, many aspects of their mechanism of action remain unclear, in particular the emergence and role of collective phenomena such as the spontaneous formation of nano-sized unstructured objects (clusters) and their effects on the biodynamics. We study this process using two novel peptides from the mucus of the garden snail Cornu aspersum as an example to reveal its dynamics and bioactivity implications through coordinated in silico and in vitro techniques — molecular dynamics simulations, UV–Vis and fluorescence spectroscopy, and antibacterial activity tests against two representative bacterial strains — one gram-negative (Escherichia coli 3458) and one gram-positive (Bacillus subtilis). The results obtained confirm the impact of the aggregation processes of the peptides on their biological activity and provide insight into possible synergies in their action.